The Corrected Interpretations of the Five Classics (Wujing zhengyi) and the Tang Legacy of Obscure Learning (Xuanxue). - Bender, Lucas Rambo (T'oung Pao, 2019)
The Corrected Interpretations of the Five Classics (Wujing zhengyi) is a surprisingly neglected source for the study of medieval Chinese intellectual history. Often considered more of a political performance than an intellectual one, the series has been charged with heterogeneity in its attempt to put an end to the intellectual disputes of the period of division and to craft an orthodoxy for the nascent Tang dynasty. This paper will show, however, that the Zhengyi subcommentaries do articulate a coherent intellectual position with regard to a set of crucial questions about the cosmos, the ancient sages, and the culture that they inaugurated. Repurposing xuanxue arguments about the inherent obscurity of the dao and the cosmos, the Zhengyi argues that most of us cannot understand the source of normative values, and that therefore our only recourse is to limit our intellectual presumptions and follow the models provided by the ancient Sage Kings.